Nucleation and growth: modeling the NH3 - HCL reaction - Shinn, Jaime M., author; Shipman, Patrick, advisor; Liu, James, committee member; Mueller, Jennifer, committee member; Thompson, Stephen, committee member (Colorado State University. Libraries, 2012)
One of the trademarks of a Liesegang ring system is the exhibition of a moving reaction front to form a periodic precipitation pattern. This phenomenon has been studied by both chemists and mathematicians. The periodic patterns produced have developed an interest from a mathematical perspective, while the theory and mechanism behind these patterns has created interest from a chemist's point of view. Many mathematical models have been proposed, and much interest has been invested in studying the mechanism behind these Liesegang ring systems. In particular, we will consider the NH3-HCl system, a gas-phase system in which the two gases (NH3 and HCl) diffuse into a tube and meet to form a solid precipitate. The reaction front then moves down the tube, forming a Liesegang banding pattern along the way. In this thesis, we derive a model for this system and examine some results of the model, which contribute to the theory and mechanism behind the NH3-HCl system. We predict the position of the first and last Liesegang band formed, and we examine the effect of the tube length of our system. Front velocity data from the model has also been obtained and is shown to correlate well with experimental data. We also note that the width of the heterogeneous nucleation zone increases as the concentration ratio of NH3 to HCl decreases, and we discuss the effect that water vapor has on the system.